Dukungan Suami Bukan Faktor Utama Kualitas Hidup Akseptor KB IUD - Bella Putri Prastika; Ni ketut Alit Arimi; Retnayu Pradanie (Pediomaternal Nursing Journal, 2019)
Introduction: The use of low IUD can affect the quality of family life. One of the reasons for using KB is because of the expensive number of children, which is a mayor influence for couples of childbearing ages in improving their welfare. The lower the use of contraception, the lower the quality of life of IUD KB acceptor. The purpose of this study was to explain the relationship between husband’s support and the quality of life of family planning acceptors.Methods: The design of this study is correlational with a cross-sectional approach. The population in this study were acceptors of IUD KB in the Mulyorejo Health Center Surabaya Working Area. The sample of 92 women of childbearing age acceptors of IUD KB was obtained by purposive sampling. Independent partners support variable. The dependent variable is the quality of life status. Data collection using partners support questionnaire and quality of life according to WHOQOL-BREF. Test statistics with Spearman's rho test.Results: There was no significant relationship between lifestyle and quality of life (p = 0.421, r = 0.085).Conclusion: The husband’s most supportive was that they supported the use of family planning. The factor of husband’s support related to quality of life is emotional support, intellectual support, appreciation support, and information support. The majority of respondents can play an independent role in improving their quality of life, starting from making the best decisions for their health in the use of IUD KB. Husband’s support is not always the biggest contributor to improving quality of life, but there are other factors that need to be considered. Further research is needed on other factors related to the quality of life of family planning acceptors.